Pigeon Stories: Review of Colin Jerolmack, The Global Pigeon - Holmberg, Tora (Humanimalia, 2013)
Colin Jerolmack. The Global Pigeon. Fieldwork Encounters and Discoveries. Chicago: The University of Chicago Press, 2013. 288 pp. 80.00 hb; 27.50 pb; 7.00-27.00 e-bk.